A perspective on algae, the environment, and energy. Issue 4 (2nd September 2013) - Savage, Phillip E.; Hestekin, Jamie A.
<x xml:space="preserve">Abstract</x> Aquatic biomass, in general, and algae, in particular, are gaining attention for wastewater treatment and as a feedstock for renewable fuels. Research into algae biofuels is receiving significant attention because of the potential for providing high amounts of fuel with low land use. Several obstacles still remain especially in the area of algae selection, bioreactor choice, conversion to fuel precursors, and ultimate fuel production. This special issue of Environmental Progress and Sustainable Energy focuses on these issues and recent work that moves the field toward environmentally sustainable algae production. © 2013 American Institute of Chemical Engineers Environ Prog, 32: 877–883, 2013